Que escola é precisa para aprender, sem pôr em perigo o bem estar e as relações interpessoais dos adolescentes - Tomé, Gina (2019)
The aim of the present study was to analyse the association between school, interpersonal relationships and the wellbeing of Portuguese adolescents. A total of 5695 Portuguese adolescents with a mean age of 15.46 (SD=1.80), attending the 8th, 10th and 12th years of schooling in mainland Portugal were included in the Health Behavior in School-aged Children (HBSC) study.: A path analysis model was carried out in order to verify the association between the school satisfaction, wellbeing and the interpersonal relationships of Portuguese adolescents. There was a significant and positive association between school satisfaction and the relationship with family, relationship with friends and relation with teachers. Concerning wellbeing, there was a significant and positive association with life satisfaction and happiness and a significant and negative association with psychological symptoms, social alienation and concerns. These results highlight the role of contexts for adolescent satisfaction with school, like the importance of the relationship with family and friends, especially the role of teachers and, on the other hand, the influence of school on the wellbeing of adolescents, showing that the more they like school, the greater is the wellbeing of adolescents. In order to promote the adolescents’ school satisfaction and consequently their wellbeing, it is essential to design interventions that include all the agents involved in the education and development of adolescents in Portugal, as well as to change the focus of the school also for the promotion of personal, social and emotional skills of adolescents.